Implementation and control of a high gain boost DC-DC converter with continuous input and output currents - Tan, Terence Wei Ren (Nanyang Technological University, 2023)
This paper present the design, implementation and control of a new high gain(NHG) quadratic boost converter. The NHG boost converter is an improved version of the traditional boost converter that offers a significantly high voltage gain ratio without utilising any transformer. To regulate the NHG boost converter, three controllers are integrated. They are sliding mode controller, the adaptive current mode controller and the non adaptive current mode controller. Experimental results are presented to show the performance of the controllers for the changes in reference voltage and load resistance.